Prevalence of temporomandibular disorders in MBBS students – A study from north India - Bhatia, Sanjiv; Singh, Pratipal; Kumar Goel, Vijay; Uraiya, Dharmendra; Kumar, Ajay (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2020)
Introduction: The Fonseca questionnaire is a self-administered questionnaire that has been proposed as a low-cost, easily applied alternative TMD assessment tool for the non-patient population. It serves as a preliminary screening tool for TMD. Material and methods: It was a cross-sectional descriptive study conducted by the general surgery department ofHind Institute of Medical Science, Safedabad, Barabanki, Uttar Pradesh from March 2018 to May 2018. The minimum sample size required for the study was found to be 360 to obtain CI level of 0.95, at least 80% power for analysis and minimal error. The sample size was kept to be 450 as the students volunteered for the research. Results: The most common symptom was pain on neck or neck stiffness seen in 30% of the males and 47 % females, second most common symptom found was the habit of clenching or grinding the teeth seen in 26% of the males and 33% of the females. Regarding the presence of TMDs, 60% of the participants were scored to have mild TMD, 4.7% were scored to have moderate TMD sand only 1.5 % were scored to have severe temporomandibular disorders. Conclusion: A simple Anamnestic index is of use in identifying and classifying TMJ and TMD symptoms in patients according to the severity of the disorder. Identification and follow-up of the prevalence and health-care needs of patients with TMDs are recommended with longitudinal studies.